(untitled) (The Development of Humanities and Social Sciences, 2026)
The world’s top four research university alliances were selected as research objects, and comparative analysis method was used to compare and analyze the scientific research productivity, scientific research influence and cooperation, and discipline group structure of the university alliances. The overall profile and main characteristics of the disciplines of the university alliances would reveal the gaps and characteristics of the disciplines of the international top university alliances. The research results show that the IVY University Alliance has the highest impact on standardized citations and the impact of disciplines relative to the global average level. The RG university alliance has the highest number of scientific research papers and the highest degree of international cooperation papers.The paper output of the C9 university alliance increased the fastest. The four university alliances differ greatly in the presentation of the discipline group structure.：Among the superior disciplines of the IVY, RG, and Go8 university alliances, clinical medicine has the most outstanding performance. The C9 university alliance has the most outstanding performance in material science.The study found that maintaining close links between scientific research and international frontiers, optimizing the structure of disciplines, and creating more peaks in discipline clusters have important enlightenment values for the development of university alliances.